2001
DOI: 10.1007/s003300100987
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of vesicoureteral reflux with colour Doppler sonography in adult patients with spinal cord injury

Abstract: The aim of the study was to evaluate prospectively the performances of colour Doppler sonography for detection of vesicoureteral reflux in adult patients with neurogenic bladder due to spinal cord injury. One hundred eighty-seven adult patients who had developed neurogenic bladder due to spinal cord injury underwent retrograde cystography and sonographic evaluation by B-mode and colour flow Doppler sonography (CFDS). Results of both examinations were analyzed independently by two radiologists. Representative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…18 In adults with neurogenic bladder, color Doppler ultrasonography can detect reflux. 19 Whether upper tract deterioration is inevitable in SCI patients, as they age, is an unanswered question. A prospective study of 199 patients with SCI who were an average of 33 years after injury, showed a decline in renal function regardless of method of bladder management.…”
Section: Imaging Of Upper Tracts In Patients With Bladder Dysfunctionmentioning
confidence: 99%
“…18 In adults with neurogenic bladder, color Doppler ultrasonography can detect reflux. 19 Whether upper tract deterioration is inevitable in SCI patients, as they age, is an unanswered question. A prospective study of 199 patients with SCI who were an average of 33 years after injury, showed a decline in renal function regardless of method of bladder management.…”
Section: Imaging Of Upper Tracts In Patients With Bladder Dysfunctionmentioning
confidence: 99%